STUDENTS’ PERCEPTION OF THE LECTURER’S EMOTIONAL SUPPORT IN ONLINE LEARNING - ROWI HARNOMAN (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: Online learning enforces most direct instruction into online and distance learning. However, good preparation and readiness in online learning is necessary in order to be effectively implemented. The transition from traditional to virtual classrooms, gives some challenges in maintaining social and emotional competencies for the continuation of good relationships in learning. Therefore, the researcher is interested in conducting a study about what kinds of emotional support provided by lecturers in online learning based on students’ perception as well as the students' expectation of lecturers' emotional support in online learning. This research is conducted using descriptive qualitative on 10 students from the 7th semester in English language department at the University of Islam Malang because at 7th semester using self-constructed semi-structured interviews consisting of 10 interview questions. The data collected via online interview through Zoom twice and analyzed by qualitative data analysis that include reduction, coding, organizing, synthesize, and interpretation. The result indicated that the lecturers provide emotional support by actively motivate, give constructive feedback about the students' learning competence, try to maintain the class equity, guide the students about respect and pay attention to students' learning attitude, guiding the students about being responsible, and involving the students in discussion and decision making. The students believe that good emotional support should reflect a good relationship between the lecturers and students as well as make the class more enjoyable. Moreover, good emotional support can be established if motivation, attention, feedback, respect, equality, responsibility, attitude, and appreciation as well as communication are emotionally supported by the lecturers. Other than that, it is important to consider students’ learning difficulties and individual difference to maintain harmony in the classroom.Key Words: : Emotional support, online learning, perception.